2007
DOI: 10.1128/aac.00029-07
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Ceftobiprole and Comparators to the Penicillin-Binding Proteins of Escherichia coli , Pseudomonas aeruginosa , Staphylococcus aureus , and Streptococcus pneumoniae

Abstract: Ceftobiprole exhibited tight binding to PBP2a in methicillin-resistant Staphylococcus aureus, PBP2x in penicillin-resistant Streptococcus pneumoniae, and PBP3 and other essential penicillin-binding proteins in methicillin-susceptible S. aureus, Escherichia coli, and Pseudomonas aeruginosa. Ceftobiprole also bound well to PBP2 in the latter organisms, contributing to the broad-spectrum antibacterial activity against gram-negative and gram-positive bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(139 citation statements)
references
References 28 publications
9
127
3
Order By: Relevance
“…Our data show that acidic pH causes a significant change in conformational behavior of PBP 2a, rendering it more susceptible to ␤-lactams. In terms of mechanistic consequence, we assert that these observations are quite similar to those recently reported for new cephalosporins that are capable of inhibiting PBP 2a effectively, arguing for an underlying principal that governs both cases (22)(23)(24).…”
Section: Methicillin-resistant Staphylococcus Aureus (Mrsa)supporting
confidence: 68%
“…Our data show that acidic pH causes a significant change in conformational behavior of PBP 2a, rendering it more susceptible to ␤-lactams. In terms of mechanistic consequence, we assert that these observations are quite similar to those recently reported for new cephalosporins that are capable of inhibiting PBP 2a effectively, arguing for an underlying principal that governs both cases (22)(23)(24).…”
Section: Methicillin-resistant Staphylococcus Aureus (Mrsa)supporting
confidence: 68%
“…All ceftobiprole MIC values were 2 µg/mL for 146 isolates of S. aureus including MSSA (MIC 90 , 1 µg/mL) and MRSA (MIC 90 , 2 µg/mL). Denis et al 6 reported ceftobiprole MIC 50 and MIC 90 values of 0.5 and 2 µg/mL, respectively against MRSA. Of a total of 1201 S. aureus (66% MRSA) and 460 CNS single-patient isolates, ceftobiprole MICs ranged from 0.12 to 1 µg/mL for MSSA and 0.25 to 4 µg/mL for MRSA.…”
Section: Staphylococcus Speciesmentioning
confidence: 99%
“…Ceftobiprole exhibits a binding profile similar to those of cefepime and ceftazidime in Pseudomonas aeruginosa but with an enhanced binding to PBP2. 6 This profile contributes to the broad-spectrum antibacterial activity against gram-negative and grampositive bacteria of this cephalosporin. No breakpoints have been established for ceftobiprole, but based on minimum inhibitory concentration (MIC) distribution and pharmacokinetic/pharmacodynamic information, Mouton et al 7 proposed a provisional breakpoint of 4 µg/mL for susceptible Gram-positive microorganisms.…”
Section: In Vitro Antibacterial Activity: Ceftobiprole and The Penicimentioning
confidence: 99%
See 1 more Smart Citation
“…However, drug molecules with TPSA values of 140 Å or higher are expected to have very low absorption [26]. Lipophilicity (miLogP) and TPSA values are essential factors for the prediction of oral bioavailability of drugs [29]. Molinspiration cheminformatics are available from http://www.molinspiration.com.…”
Section: Molinspiration Calculationsmentioning
confidence: 99%